Leadership and Operational Indexes for Supply Chain Resilience - Mendoza Solis, Maribel; García-Alcaraz, Jorge Luis; Madrid Solórzano, Juan Manuel; Jiménez Macías, Emilio (Springer, 2023)
https://link.springer.com/book/10.1007/978-3-031-32364-5#toc